The place of periodontal examination and referral in general medicine. Issue 1 (21st April 2017) - Chan, Samuel; Pasternak, Graham M.; West, Malcolm J.
Abstract: In many countries, dental services, unlike other health‐care services, are not covered by the principle of universal access. It is only in the last couple of decades that there has been a greater interaction between medicine and dentistry. Various health‐care systems worldwide may provide public dental services to the young and the disadvantaged, but few provide access to all. Public policy does not appear to appreciate the vast economic, health and social implications of poor oral health on the overall health of an individual. Recognizing and acting on the interrelatedness between oral health and overall health helps to protect patients from pathological diseases, such as infective endocarditis, suboptimal glycemic control and deterioration in renal function. This review article examines some of the medical conditions to which patients are predisposed as a result of poor dental care. Additionally, the paper provides some real‐life case examples to support this hypothesis, reinforces the importance of a strong relationship that needs to be embedded between the dentist and the physician and finally provides some suggestions for a multidisciplinary approach.